The “CS” (reduced comfort level) Housing Programme: The elimination of Gypsy settlements and shanty towns during the socialist period in Hungary - TAMÁS ATTILA HAJNÁCZKY (Romani Studies)
The aim of this paper is to describe the single party-state’s Gypsy settlement elimination programme in socialist Hungary. In the course of the research, I relied mainly on decrees and reports issued by the local council apparatus as “secret dossiers” and on sociological studies from the period. The ideological background of the communist state’s Gypsy settlement elimination programme, the so-called “CS-housing” programme (CS = reduced comfort level), was as follows: the Hungarian Socialist Workers’ Party did not recognize the Hungarian Gypsies as a nationality and announced a policy of forced assimilation for them. The assimilation of the Gypsy population was mainly envisaged through the dismantling of their settlements and the dispersal of Gypsies among non-Gypsies. During the nearly two and a half decades of the CS-housing programme, more than 35,000 housing units were allocated, and most of the Gypsy settlements were dismantled. However, new forms of segregation emerged: ghettoized villages and segregated CS-housing settlements. In the last years of the socialist regime, it became clear that the single party-state’s policy of forced assimilation of Gypsies had failed, and that the segregation of Gypsies could not be eliminated, partly due to the failures of the CS-housing programme. Furthermore, some village and town councils prevented the dispersal of the Gypsy settlers among the non-Gypsy population and created “more modern Gypsy settlements” for them. This article was published open access under a CC BY-NC-ND licence: https://creativecommons.org/licences/by-nc-nd/4.0/.